Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Kemampuan Berpendapat - Hastuti, Eka Fitri (JURNAL PESONA, 2017)
AbstractThe aim of this study is to improve students ability on expressing opinions in Indonesian subject through STADÂ cooperative learning model in the fourth grade SDN 01 Adirejo Academic Year 2016-2017. It is a classroom action research that completed in two cycles and each cycle consisted of four stages: planning, action, observation, and reflection. The conclusion showed that STAD cooperative learning model improves the students ability on expressing opinions in Indonesian subjects fourth-grade students of SDN 01 Adirejo Academic Year 2016-2017.Keywords: Ability Argues, Cooperative Learning, Model Teams-Student Achievement Division (STAD)